Targeting Tubulin-colchicine Site for Cancer Therapy: Inhibitors, Antibody-Drug Conjugates and Degradation Agents - Duan, Yongtao; Liu, Wei; Tian, Liang; Mao, Yanna; Song, Chuanjun (Current Topics in Medicinal Chemistry, 2019)
Microtubules are essential for the mitotic division of cells and have been an attractive target for antitumour drugs due to the increased incidence of cancer and significant mitosis rate of tumour cells. In the past few years, tubulin-colchicine binding site, as one of the three binding pockets including taxol-, vinblastine- and colchicine-binding sites, has been focused on to design tubulin-destabilizing agents including inhibitors, antibody-drug conjugates and degradation agents. The present review is the first to cover a systemic and recent synopsis of tubulin-colchicine binding site agents. We believe that it would provide an increase in our understanding of receptor-ligand interaction pattern and consciousness of a series of challenges about tubulin target druggability.
Keywords: Tubulin-colchicine binding site